Effects of sports compression socks on performance, physiological, and hematological alterations after long-haul air travel in elite female volleyballers - Broatch, J. R.; Bishop, D.; Zadow, E. K.; Halson, S. (The Journal of Strength and Conditioning Research, 2019)
The purpose of this investigation was to assess the merit of sports compression socks in minimizing travel-induced performance, physiological, and hematological alterations in elite female volleyball athletes. Twelve elite female volleyballers (age, 25 6 2 years) traveled from Canberra (Australia) to Manila (Philippines), and were assigned to 1 of 2 conditions; compression socks (COMP, n = 6) worn during travel or a passive control (CON, n = 6). Dependent measures included countermovement jump (CMJ) performance, subjective ratings of well-being, cardiovascular function, calf girth, and markers of blood clotting, collected before (224 hours, CMJ; 212 hours, all measures), during (+6.5 and +9 hours, subjective ratings and cardiovascular function), and after (+12 hours, all measures except CMJ; +24 hours and +48 hours, CMJ) travel. When compared with CON, small-to-large effects were observed for COMP to improve heart rate (+9 hours), oxygen saturation (+6.5 hours and +9 hours), alertness (+6.5 hours), fatigue (+6.5 hours), muscle soreness (+6.5 hours and +9 hours), and overall health (+6.5 hours) during travel. After travel, small-to-moderate effects were observed for COMP to improve systolic blood pressure (+12 hours), right calf girth (+12 hours), CMJ height (+24 hours), mean velocity (+24 hours), and relative power (+48 hours), compared with CON. COMP had no effect on the markers of blood clotting. This study suggests that compression socks are beneficial in combating the stressors imposed by long-haul travel in elite athletes, and may have merit for individuals frequenting long-haul travel or competing soon after flying. Abstract from author